Trends and determinants of acute tocolysis implementation in Japan, 2012–2023: An 11-year nationwide retrospective cohort study - Mikayo Toba; Rie Oi; Mutsuko Moriwaki; Masayuki Kakehashi; Ayako Fudono; Kiyohide Fushimi; Naoyuki Miyasaka (PLoS ONE, 2026)
Background International guidelines, such as those from the WHO, recommend limiting the duration of tocolysis to up to 48 hours in order to provide a window for antenatal corticosteroid administration and maternal transfer. However, reports from multiple countries indicate that tocolysis is being performed for 48 hours or longer in actual clinical settings. This study used nationwide data in Japan over an 11-year period to investigate changes in tocolytic protocol and identify factors associated with tocolysis within 48 hours. Methods Using the Diagnosis Procedure Combination database, we analyzed data from 156,356 pregnant women who received ritodrine infusion for preterm labor between April 2012 and March 2023. To accommodate day-based administrative data, we defined acute tocolysis (AT) as ≤2 and maintenance tocolysis (MT) as ≥4 days of treatment. Annual trends in AT utilization rates were examined, and logistic regression analysis was performed to identify factors associated with AT, including institutional characteristics, regional differences, and obstetric complications. Results The rate of AT utilization increased from 15.73% to 23.74% over the study period, as did variation among hospitals. University hospitals (adjusted odds ratio [aOR] = 1.16), perinatal centers (aOR = 1.12), preterm premature rupture of membranes (aOR = 3.18), and pregnancy-induced hypertension (aOR = 1.52) were associated with AT, while concomitant use of magnesium sulfate hydrate (aOR = 0.91), multiple fetuses (aOR = 0.64), and placenta previa (aOR = 0.67) were negatively associated with AT utilization. Conclusions While AT utilization has increased over time, significant disparities between facilities remain. These findings suggest that the choice of tocolytic protocol is not determined by evidence alone, but is complexly influenced by institutional roles, regional healthcare systems, and specific maternal complications. This study highlights the importance of understanding these multifaceted factors to optimize treatment strategies that balance international standards with the practicalities of individualized patient care.